Genetics of primary ovarian insufficiency. Issue 2 (12th December 2016) - Rossetti, R.; Ferrari, I.; Bonomi, M.; Persani, L.
Abstract : Primary ovarian insufficiency (POI) is characterized by a loss of ovarian function before the age of 40 and account for one major cause of female infertility. POI relevance is continuously growing because of the increasing number of women desiring conception beyond 30 years of age, when POI prevalence is >1%. POI is highly heterogeneous and can present with ovarian dysgenesis and primary amenorrhea, or with secondary amenorrhea, and it can be associated with other congenital or acquired abnormalities. In most cases POI remains classified as idiopathic. However, the age of menopause is an inheritable trait and POI has a strong genetic component. This is confirmed by the existence of several candidate genes, experimental and natural models. The variable expressivity of POI defect may indicate that, this disease may frequently be considered as a multifactorial or oligogenic defect. The most common genetic contributors to POI are the X chromosome‐linked defects. Here, we review the principal X‐linked and autosomal genes involved in syndromic and non‐syndromic forms of POI with the expectation that this list will soon be upgraded, thus allowing the possibility to predict the risk of an early age at menopause in families with POI. Abstract :